(untitled) (Medico Legal Update, 2020)
Acute poisoning is a cause of both morbidity and fatality in many parts of the world. Furadan, the organocarbamate commonly available in Kerala, being used in plantain, tea, potato and carrot farms as insecticide are usually misused as an easy source of poison for suicide. This study was carried out on Twenty nine medico legal cases, brought with history of carbamate poisoning which were brought for autopsy during the period from January 2014 to June 2015. The main objectives of the study were to study post-mortem findings in Carbamate poisoning, clinical profile in Carbamate poisoning and histopathological changes in Brain, Heart, Lungs, Liver and Kidney due to Carbamate poisoning. Males (82.8%) outnumbered females and maximum cases were of age group 51-60 yrs (27.6%). Most of the victims were taken to hospital for treatment and died after admission (58.6%). Such studies of poisoning cases will help authorities for planning, prevention and treatment of these cases